YAVOROV'S TEXTS ON GOTSE DELCHEV AS CULTURAL MEMORY IN THE SCHOOLBOOK LITERATURE UNTIL THE MIDDLE OF THE TWENTIETH CENTURY - Elena Azmanova-Rudarska (Езиков свят)
This article examines the manner in which P. K. Yavorov’s poetic and narrative works, published in educational literature between 1902 and 1909, contribute to the construction of Gotse Delchev's image. Excerpts from the biography “Gotse Delchev,” parts of the memories “Haidushki longings” (“Haidushki kopnenija”) and fragments of the lyrical cycle “Haidushki songs” (“Haidushki pesni”) are analyzed. Relevant instances of Gotse Delchev’s involvement in events of symbolic importance are used to not only trace the techniques of literary mythologizing, but also in outlining his inclusion in national history narratives. This article proposed that certain lyrical excerpts of “Haidushki songs” perform the role of ritual elements which contribute to the perception of the hero as remarkable. The research interprets the processes by which communal cultural memory functions and focuses on literary mechanisms for activating and of conditioning students’ memory. Two layers of research are thus formed – the literary text and its foundations, and the cultural aspects of historical memory. Therefore, the hermeneutic reading of the literary text in its “internal” use and the cultural analysis of the phenomenon of “memory” as the basis of culture are preferred as research methods. The image of Gotse Delchev, both on a microtextual and a macrotextual level, is entirely shaped by classical meanings and values. The main thesis of the research is that the image of Gotse Delchev was consciously and purposefully idealized in order to be turned into an active figure of the collective Bulgarian memory. This turns it into a heroic emblem for the new Bulgarian history, emphasizing the social role of textbook literature.